Dampak Covid-19 Terhadap Pendapatan Petani di Pulau Batang Dua - Sunarti Djoko; Datje Renjaan; Vernandes Taliawo (Jurnal Ilmiah Wahana Pendidikan, 2022)
The impact of the Covid -19 pandemic is being felt in all sectors, including the agricultural sector and food MSMEs. The agricultural sector is one of the priorities in dealing with the spread of Covid-19 in Indonesia. The agricultural sector must be strong in dealing with the Covid -19 pandemic because it is directly related to basic human needs. The impact of the Covid -19 pandemic that farmers feel the most is the price of farmer's products which has decreased drastically due to the decreasing purchasing power of many people. This is not comparable to the effort and operational costs incurred by farmers when cultivating. The research objective was to determine the impact of Covid-19 on the income of coconut (copra) and clove farmers on Batang Dua Island, before and during the Covid-19 pandemic on Batang Dua Island. This research is a quantitative approach. This research was carried out on Batang Dua Island which consists of 6 sub-districts where most of the population works as copra, cengke, and nutmeg farmers. The choice of research location was carried out deliberately.The impact of Covid-19 on the income of farmers on Batang Dua Island. So it can be concluded that before Covid-19 the income of copra, clove and nutmeg farmers had decreased. This has happened since the implementation of social distancing which has hampered community activities.